2019
DOI: 10.1109/tsipn.2019.2901198
|View full text |Cite
|
Sign up to set email alerts
|

Fusion Rules for Distributed Detection in Clustered Wireless Sensor Networks With Imperfect Channels

Abstract: In this paper we investigate fusion rules for distributed detection in large random clustered-wireless sensor networks (WSNs) with a three-tier hierarchy; the sensor nodes (SNs), the cluster heads (CHs) and the fusion center (FC). The CHs collect the SNs' local decisions and relay them to the FC that then fuses them to reach the ultimate decision. The SN-CH and the CH-FC channels suffer from additive white Gaussian noise (AWGN). In this context, we derive the optimal log-likelihood ratio (LLR) fusion rule, whi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
3
2

Relationship

1
9

Authors

Journals

citations
Cited by 24 publications
(9 citation statements)
references
References 37 publications
(52 reference statements)
0
9
0
Order By: Relevance
“…Indeed if we suppose that a target has a radius of influence that varies between rmin and rmax, then we can deduce the target influence area: Amin = πrmin2 and Amax = πrmax2 and by, therefore, the number (n) of sensors required to deploy in this area belongs to the interval [nmin = ρAmin, nmax = ρAmax]. On his part, Sami et al [32] consider in their research, a distributed detection in a clustered wireless sensor network deployed randomly in a large field. Results obtained showed that as the number of clusters increases, the performance rapidly reaches the Chair-Varshney benchmark for fixed SNs deployment intensity.…”
Section: G Results and Discussionmentioning
confidence: 99%
“…Indeed if we suppose that a target has a radius of influence that varies between rmin and rmax, then we can deduce the target influence area: Amin = πrmin2 and Amax = πrmax2 and by, therefore, the number (n) of sensors required to deploy in this area belongs to the interval [nmin = ρAmin, nmax = ρAmax]. On his part, Sami et al [32] consider in their research, a distributed detection in a clustered wireless sensor network deployed randomly in a large field. Results obtained showed that as the number of clusters increases, the performance rapidly reaches the Chair-Varshney benchmark for fixed SNs deployment intensity.…”
Section: G Results and Discussionmentioning
confidence: 99%
“…In this work we show that, using recently improved concentration inequalities, we can approximate the expected loss function caused by detection errors. We note that like prior works [3]- [10], we do not address the problem of optimizing sensor placement, or how to cluster existing sensors, but rather analyze the performance of existing system architectures.…”
Section: A Related Workmentioning
confidence: 99%
“…The above task both requires high performance and acceptable complexity, in order to reduce the processing power of the FC. Indeed, the latter may be also battery-powered and represent the cluster head (intermediate node) of a hierarchical fusion architecture [7], [8].…”
Section: Introductionmentioning
confidence: 99%